IMPROVING TEACHER PROFESSIONAL COMPETENCE THROUGH THE TRAINING OF INFORMATION TECHNOLOGY-BASED LEARNING MEDIA IN SOUTHEAST SULAWESI - Kadir, Abdul; Yulita, Nourma; Boulahnane, Saad (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2023)
Abstract: This article aims to improve the competence of MIPA (Mathematics and Natural Sciences) teachers using Information Technology (IT)-based learning media. A participatory action research (PAR) was conducted on twenty-five teachers from 3T regions (Frontier, Outermost, and Least Developed) of Konawe Kepulauan Regency. The findings revealed that: 1) The initial comprehension of MIPA teachers was in the low category, with an average score of 43.84. 2) The competence level of MIPA teachers after training was high, with 81.12. 3) Training using IT-based learning media effectively improved teacher competence, particularly the professional competence of teachers in the external domain. The main implementation constraints encountered by teachers were a lack of knowledge about software application installation procedures and a lack of optimality in utilizing the various features possessed by each application. Therefore, IT training is needed to improve teachers' professional competence in optimizing the use of various applications in the 3T area. Abstrak: Artikel ini bertujuan untuk meningkatkan kompetensi guru MIPA (Matematika dan Ilmu Pengetahuan Alam) dengan menggunakan media pembelajaran berbasis Teknologi Informasi (TI). Penelitian tindakan partisipatif (PAR) dilakukan terhadap dua puluh lima guru daerah 3T (Terdepan, Terluar, dan Tertinggal) Kabupaten Konawe Kepulauan. Hasil penelitian menunjukkan bahwa: 1) Pemahaman awal guru MIPA berada pada kategori rendah dengan rata-rata skor 43,84. 2) Tingkat kompetensi guru MIPA setelah pelatihan termasuk tinggi yaitu 81,12. 3) Pelatihan penggunaan media pembelajaran berbasis IT efektif meningkatkan kompetensi guru, khususnya kompetensi profesional guru pada ranah eksternal. Kendala utama implementasi yang ditemui guru adalah kurangnya pengetahuan tentang tata cara instalasi aplikasi perangkat lunak dan kurang optimalnya penggunaan berbagai fitur yang dimiliki setiap aplikasi. Oleh karena itu, pelatihan IT diperlukan untuk meningkatkan kompetensi profesional guru dalam mengoptimalkan penggunaan berbagai aplikasi di bidang 3T.